Ecological effects of reservoir operations on Blue Mesa Reservoir - Johnson, Brett M., author; Stockwell, Jason D., author; Department of Fishery and Wildlife Biology, Colorado State University, publisher (Colorado State University. Libraries, 1998)
Annual progress report, May 1, 1997-April 30, 1998.